2017
DOI: 10.1055/s-0042-118596
|View full text |Cite
|
Sign up to set email alerts
|

Verhaltensmedizinisch orientierte Rehabilitation in der Praxis

Abstract: Zusammenfassung Die verhaltensmedizinisch orientierte Rehabilitation (VOR) ist eine spezifische, multimodale Behandlungsform innerhalb der medizinischen Rehabilitation. Sie beinhaltet komplexe psychologische Interventionen, die sowohl durch Gruppen- als auch Einzeltherapien gepr?gt sind. Eine Indikation besteht f?r Patienten mit somatischen Erkrankungen, bei denen eine psychische Belastung bzw. komorbide psychische St?rung vorliegt. Die Zielgruppe im Bereich der muskuloskelettalen Erkrankungen sind Patienten m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Germany, cognitive-behavioral rehabilitation was developed for patients coping with a somatic illness who are also affected by psychological stress or comorbid psychological disorders. Cognitive-behavioral rehabilitation is a multimodal intervention that includes additional psychological and exercise interventions as compared to standard rehabilitation programs [ 9 ]. In patients with musculoskeletal disorders, randomized controlled trials revealed fewer depressive symptoms in the short and medium term among participants in cognitive-behavioral rehabilitation programs [ 10 , 11 ] and reported better pain management strategies, lower pain intensity, and better general health following cognitive-behavioral compared with standard rehabilitation programs in the long term [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, cognitive-behavioral rehabilitation was developed for patients coping with a somatic illness who are also affected by psychological stress or comorbid psychological disorders. Cognitive-behavioral rehabilitation is a multimodal intervention that includes additional psychological and exercise interventions as compared to standard rehabilitation programs [ 9 ]. In patients with musculoskeletal disorders, randomized controlled trials revealed fewer depressive symptoms in the short and medium term among participants in cognitive-behavioral rehabilitation programs [ 10 , 11 ] and reported better pain management strategies, lower pain intensity, and better general health following cognitive-behavioral compared with standard rehabilitation programs in the long term [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%